Analysis and Design of Distribution Systems Information Flow in the Sugar Supply Chain in Indonesia - Ekawati, Ratna; Arkeman, Yandra; Suprihatin, Suprihatin; Sunarti, Titi Candra (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Today's modern supply chain represents a complex and real-time, organization, resource, activity, information, and data source that is involved in the distribution of products and services ranging from upstream to downstream of the supply chain. In the past 4.0 supply chain technology was not just a linear business function, but as the center of the main process of ecosystems that are in a blind spot chained by value. With information as a foundation in the decision-making process so that information can create integrated and efficiently coordinated supply chains. So that it can show continuity from planning to production, inventory, quality, and price control in each chain. An inefficient distribution that results in mistrust among stakeholders, because it has an impact on the decline and loss of value chain in quality and quantity. Integrity problems from the data collected were found in this study. These findings include the identification of various stakeholders, including farmers, importers to customers, and regulators, as well as their needs, which will be described through the use case, and BPMN. The results obtained are that the main actors (stakeholders) of the system are divided into farmers, importers, processing factories, headquarters, hauling services, and markets (customers) in the distribution of product information flow systems. Suggests tracking and tracing based on real-time data flow of product information coming from each actor in the sugar supply chain that is equipped with an accurate data distribution information support system.